2013
DOI: 10.1177/0192636513514110
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Challenges in Addressing Changing Demographics in Schools

Abstract: Principals who lead demographically diverse schools play an important role in changing the dynamics that often occur in these contexts. Consequently, principals must have the leadership skills to revolutionize teachers’ belief systems. Their energies are consumed with reshaping teachers’ instructional practices and focusing on improving student expectations. Teachers may oppose modification of their teaching practices due to fears of letting go of familiar ways of teaching. The inability to influence teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
(29 reference statements)
0
12
0
1
Order By: Relevance
“…To address feelings of isolation that can sometimes occur when working in majority White districts, some schools offer support groups to provide safe spaces in which teachers of color can share their experiences with each other and with administrators (Delpit, 2006;Preis, 2017). Districts seeking to increase their proportions of minority educator must not only make intentional recruitment efforts but also address retention by insuring that staff feel nurtured, safe, and valued by their school communities (Madsen & Mabokela, 2014).…”
Section: Improving Hiring and Retention Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…To address feelings of isolation that can sometimes occur when working in majority White districts, some schools offer support groups to provide safe spaces in which teachers of color can share their experiences with each other and with administrators (Delpit, 2006;Preis, 2017). Districts seeking to increase their proportions of minority educator must not only make intentional recruitment efforts but also address retention by insuring that staff feel nurtured, safe, and valued by their school communities (Madsen & Mabokela, 2014).…”
Section: Improving Hiring and Retention Practicesmentioning
confidence: 99%
“…Principals must provide encouragement and oversight to insure the implementation of the changes in practice identified through professional development (Johnson & Uline, 2005). They need to build relationships with staff that will allow for difficult discussions and ongoing dialogue about improving practices around equity (Madsen & Mabokela, 2014). They need to recognize and manage undermining influences such as rigid course pacing expectations, scheduling interruptions, colleague and parent pressure, and student absenteeismall of which can cause a default back to former unproductive practices (Torff, 2011).…”
Section: Building Leader Capacity and Sustainability Establishing Accmentioning
confidence: 99%
See 1 more Smart Citation
“…When the principals are unable to influence educators positively, continual problems of low expectation, unfair discipline practices and poor learner performance will be encountered (Madsen & Mabokela, 2013). In a qualitative research study conducted among school principals in South Africa, to determine causal factors of ineffective management in schools, Msila (2011) found that of the 56 principals participated in the study, majority cited that the democratic policies that are entrenched by Teachers' Unions also contribute to their inefficiency and ineffectiveness to perform their duties without being intimidated.…”
Section: Ineffective Communication Among Educatorsmentioning
confidence: 99%
“…Palabras clave: estudiantes de inglés; percepciones de los directores; liderazgo escolar; programas de segundo idioma His study presented here examines 22 elementary school principals' knowledge of the bilingual/second language programs that are implemented at their schools that are located in a metropolitan school district located in the south central region of the United States and serves many English Language Learners (ELLs). As the number of ELLs continues to increase in many regions of the US, elementary school educators are faced with the critical challenge of providing them an appropriate education (Madsen & Mabokela, 2014;Timberlake, Howell, & Staight, 2011). While teachers must provide effective instruction for ELLs so that they are successful in learning English and academic content (Short & Fitzsimmons, 2007), principals must also have the critical knowledge needed to support teachers in working with ELLs (Darling-Hammond, 2010;Graczewski, Knudson, & Holtzman, 2009).…”
Section: Introductionmentioning
confidence: 99%